Prevalence of Non-Tuberculous Mycobacteria in Hospital Waters of Major Cities of Khuzestan Province, Iran - Khosravi, Azar Dokht; Hashemi Shahraki, Abdolrazagh; Hashemzadeh, Mohammad; Sheini Mehrabzadeh, Rasa; Teimoori, Ali (Frontiers in Cellular and Infection Microbiology, 2016)
Nontuberculous mycobacteria (NTM) are among the emerging pathogens in immunocompromised individuals including hospitalized patients. So, it is important to consider hospitals water supplies as a source for infection. The aim of this study was to determine the prevalence of NTM in the hospital aquatic systems of Khuzestan, South west of Iran. In total, 258 hospital water samples were collected and examined. After initial sample processing, sediment of each sample were inoculated into two Lowenstein-Jensen medium. The positive cultures were studied with phenotypic tests including growth rate, colony morphology, and pigmentation, with subsequent PCR- restriction enzyme analysis (PRA) and rpoB gene sequence analysis. Mycobacterial strains were isolated from 77 samples (29.8%), comprising 52 (70.1%) rapid growing, and 25 (32.4%) slow growing mycobacteria. Based on the overall results, M. fortuitum (44.1%) was the most common mycobacterial species in hospital water samples, followed by M. gordonae (n=13,16.8%) and M. senegalense (n=5, 7.7%). In conclusion, current study demonstrated the NTM strains as one of the major parts of hospital water supplies with probable potential source for nosocomial infections. This finding also help to shed light on to the dynamics of the distribution and diversity of NTM in the water system of hospitals in the region of study.